Design and development of a small-scale 12S-14P outer rotor HEFSM - M.Romalan, Gadafi (2016)
Simulation, prototype experimental, and mathematical modelling is an essential process to provide sufficient evidence before a full-scale development or mass production. Hence, this study focuses on validating a small scale of 12S-14P outer-rotor hybrid excitation flux switching motor (OR-HEFSM) through simulation, experimental, and mathematical modelling. The JMAG-Designer software as finite element solver is used to design and analyse the designed geometry structure. Throughout simulation process, the rotor design with direct drive structure as illustrated in Appendix A is chosen based on optimisation process. Thus, the generated back EMF, torque, and power through simulation at a speed of 1,200 r/min is 6.58 V, 16.4 Nm, and 12.4 kW, correspondingly. The designed model has been fabricated using actual prototype analysis (APA) approach, which is involves five stages, namely 3-D design, material selection, fabrication, assembly, and experimental test. The computer-aided software of SolidWorks is used to implement the first stage of APA while the prototype structure is fabricated using a computer numerical control (CNC) machine. The prototype has been tested experimentally using a measurement tool such as Fluke Analyser and oscilloscope. The back EMF showed a good agreement between simulation and preliminary experimental results with percentage differences approximately 5.1% at a speed of, 1,200 r/min. In contrast with the prediction results based on mathematical modelling using sizing equation, the calculated back EMF, torque, and power is 7.58%, 8.6%, and 8.4% higher than simulation results, respectively. Even so, the results had proven that the concept of three-phase working principle for small-scale 12S-14P OR-HEFSM with direct drive structure remained the same for simulation, experiment, and prediction.